(untitled) (Medico Legal Update, 2020)
Breast cancer is the most common cancer in women both in the developed and less developed world In Iraq, it is the commonest type of female malignancy, accounting for approximately one-third of the registered female cancers according to the latest Iraqi Cancer Registry. A descriptive cross-sectional study was conducted on working women in Kirkuk Technical Institute during the period from 1st April till 30th June / 2016 to assess their knowledge regarding breast cancer prevention and control methods. The total number of included studied women was 71from different scientific departments after distributing a special questionnaire form and face to face interview was done after receiving the written agreements to participating in the study. Majority of working women are technical (52.2%), married (74.7%) aging above 40 years (47.8%) with employment years above 15 years (50.0%). Both electrical and survey dept. go with the establishing of breast cancer prevention at adulthood after fully maturated (44%, 45%) respectively in comparison to 57.7% of study women from electronic dept. go with the starting of cancer prevention at the birth of a first child . The main recommendation of the study is that further researches should be done because there is a need for increased efforts towards developing and widely available cancer educational program that focuses on the main preventive measures and encouraging the women with breast disease, not only providing them with information but also for the ability to make her decision to control the disease